Genome-wide association study: Understanding the genetic basis of the gait type in Brazilian Mangalarga Marchador horses, a preliminary study - Bussiman, Fernando de Oliveira; Aparecida dos Santos, Bruna [UNESP]; Abreu Silva, Bárbara da Conceição; Mamani, Gerardo Cornelio Mamani; Grigoletto, Laís; Pereira, Guilherme Luis [UNESP]; Ferraz, Guilherme de Camargo [UNESP]; Ferraz, José Bento Sterman; Mattos, Elisângela Chicaroni; Eler, Joanir Pereira; Ventura, Ricardo Vieira; Curi, Rogério Abdallah [UNESP]; et al. (Elsevier, 2020)
The ECA23:22999655C>A DMRT3 variant has been described as a causative region for the four-beat gait in horses, however it remains uncertain for the two distinct gait types observed in the Brazilian Mangalarga Marchador (MM) breed. This study aimed to perform a single-step GWAS, prospecting the genetic architecture of the marcha batida (MB) and marcha picada (MP) in MM horses. Phenotypic records from 1,230 animals in a pedigree file containing 3172 individuals were considered in the current analysis. A total of 192 (86 MB and 106 MP) horses were genotyped with the 670 k equine genotyping array (Thermo Fisher Scientific), and 48 horses were imputed from 65k (Illumina) to 670k. The GWAS was conducted in a Bayesian approach. For the estimation of SNP effects, three iterations were performed. The position from SNPs that explained more than 1% of the additive genetic variance were used to prospect genomic regions in windows of 250 kb. From the 69 identified genes, 39 were not annotated in horses and were blasted against the NCBI database. The enrichment analysis revealed that eight metabolic pathways might be involved with the gait type since most were related to the metabolism of amino acid, energy, and immune system. The found genes were associated with differences in the energetic metabolism between animals from the marcha batida or marcha picada groups, as well as with metabolic changes after gait exercise.
Keywords: External stimuli; Gait metabolism; Horse; Single-step GWAS